Association Between Influenza Vaccine and Immune Thrombocytopenia: A Systematic Review and Meta-Analysis - Zhicai Liu; Jing Wang; Zhaojun Lu; Yuyang Xu; Jian Du; Jiayin Han; Xuechao Zhang; Yan Liu (Vaccines)
Background: Immune thrombocytopenia (ITP) is an uncommon but serious adverse reaction after vaccination. However, its association with vaccines other than the measles–mumps–rubella vaccine remains debatable. This study aimed to analyze ITP cases following influenza vaccination and assess any potential association. Methods: We performed a systematic search of the Web of Science, Embase, and PubMed databases from their inception to 15 April 2024. Cases were characterized qualitatively, and relative risk was assessed using either fixed or random models. Results: A total of 24 studies were analyzed, including 16 patients from 14 case reports. Patients averaged 56.7 years old, half were female, and ten patients had a history of prior illness. The mean time between vaccination and diagnosis was 13.3 days. Treatment primarily involved corticosteroids or intravenous immunoglobulin, with most recovering within a month. The pooled odds ratio for ITP post-influenza vaccination was 0.94 (95%CI: 0.85–1.03). Subgroup analyses conducted according to the study design and vaccine type did not reveal any significant results. Conclusion: No evidence of an association between influenza vaccination and ITP was found. Further observational studies are required to verify this relationship.